2020
DOI: 10.1097/pai.0000000000000857
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Study of PD-L1 SP142 Assay in Metastatic Triple-negative Breast Cancer

Abstract: Metastatic triple-negative breast cancer (mTNBC) is the most aggressive breast cancer subtype. Programmed death ligand 1 (PD-L1) on immune cells (IC) using the VENTANA SP142 assay is linked to improved clinical outcome in atezolizumab plus nab—paclitaxel-treated patients with mTNBC in the IMpassion130 study. The goal of the current study was to evaluate prevalence of VENTANA SP142 PD-L1 assay by anatomic location in 670 histologically confirmed TNBC cases from subjects with metastatic disease screened for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 27 publications
(44 reference statements)
3
29
0
Order By: Relevance
“…Similarly, subgroup analysis according to antibody used for PD-L1 assessment was only possible for SP142 clone. When analyzed regardless of cell of expression and IHC subtype, the pooled PD-L1 positivity rate according to SP142 was higher at the primary tumor (44.4%, 95% CI: 29.8-59.5, I 2 = 98.2%) than in metastatic tissue (28.4%, 95% CI: 17.8-40.2, I 2 = 80%; p < 0.001) [14,21,22,24,26,30,35,36].…”
Section: Pd-l1 Protein Expression In Primary Tumor and Metastasis In Subgroups Of Interestmentioning
confidence: 96%
See 3 more Smart Citations
“…Similarly, subgroup analysis according to antibody used for PD-L1 assessment was only possible for SP142 clone. When analyzed regardless of cell of expression and IHC subtype, the pooled PD-L1 positivity rate according to SP142 was higher at the primary tumor (44.4%, 95% CI: 29.8-59.5, I 2 = 98.2%) than in metastatic tissue (28.4%, 95% CI: 17.8-40.2, I 2 = 80%; p < 0.001) [14,21,22,24,26,30,35,36].…”
Section: Pd-l1 Protein Expression In Primary Tumor and Metastasis In Subgroups Of Interestmentioning
confidence: 96%
“…1, while the detailed documentation of the search strategy is provided as Supplementary Data. Using this selection strategy, 20 studies were included in the metaanalysis [14,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The study characteristics are presented in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of TILs was lower in metastasis compared with PBC, especially TNBC showed the most decrease (5% in BCBM, 20% in PBC; p = 0.022) [ 124 ]. Li et al reported a higher prevalence of PD-L1 expression on immune cells in the brain compared to the liver and bone (50.0% in the brain, 26.9% in the liver, and 25.0% in bone) [ 125 ], however, the number of patients with BMs is limited to four and it is not a definitive.…”
Section: Systemic Therapy For Bcbmmentioning
confidence: 99%